2015
DOI: 10.1002/chin.201513197
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Organocatalytic Asymmetric Inverse‐Electron‐Demand 1,3‐Dipolar Cycloaddition of N,N′‐Cyclic Azomethine Imines.

Abstract: The first organocatalytic asymmetric inverse-electron-demand 1,3-dipolar cycloaddition of the title imines (I) is described. Chiral bicyclic pyrazolidin-3-one derivatives (III) (18 example) are thus obtained in excellent diastereoselectivity and good enantioselectivity. -(ZHU, R.-Y.; WANG, C.-S.; ZHENG, J.; SHI*, F.; TU, S.-J.; J. Org. Chem. 79 (2014) 19, 9305-9312, http://dx.doi.org/10.1021/jo5018469 ; Sch. Chem. Chem. Eng., Jiangsu Norm. Univ., Jiangsu, Xuzhou 221116, Peop. Rep. China; Eng.) -R. Staver 13-197 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Shi and co-workers developed chiral phosphoric acid-catalyzed inverse electron demand 1,3-DC of N , N ′-cyclic azomethine imines (Scheme ) . A unique feature is the use of vinylphenols 136 as dipolarophile with which cycloadducts 137 having a quaternary center were obtained in moderate yields and enantioselectivities.…”
Section: Azomethine Iminementioning
confidence: 99%
“…Shi and co-workers developed chiral phosphoric acid-catalyzed inverse electron demand 1,3-DC of N , N ′-cyclic azomethine imines (Scheme ) . A unique feature is the use of vinylphenols 136 as dipolarophile with which cycloadducts 137 having a quaternary center were obtained in moderate yields and enantioselectivities.…”
Section: Azomethine Iminementioning
confidence: 99%
“…5 Since the first report of catalytic asymmetric 1,3-DC using N,N′-cyclic azomethine imines reported by Fu's group, 6 several asymmetric 1,3-DC reactions of α,β-unsaturated carbonyl compounds with azomethine imines involving the organometallic and organocatalysts have been developed. 7,8 In 2007, Suga et al reported highly diastereoselective and enantioselective 1,3-DC between azomethine imines and 3-acryloyl-2-oxazolidinone catalyzed by the binaphthyldiimine−Ni(II) complex (Scheme 1a). 9 In 2013, Wang and co-workers developed chiral bis-phosphoricacid-catalyzed asymmetric 1,3-DC of methyleneindolinones and N,N′-cyclic azomethine imines to synthesize enantiomerically pure spiro[pyrazolidin-3,3′-oxindoles] for the first time (Scheme 1b).…”
mentioning
confidence: 99%